2022
DOI: 10.3390/nu14071440
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Properties and Use of Extra Virgin Olive Oil in Clinical Nutrition: A Narrative Review and Literature Update

Abstract: Extra virgin olive oil (EVOO) is a cornerstone of the Mediterranean diet (MedD). In this narrative review, we synthesize and illustrate the various characteristics and clinical applications of EVOO and its components—such as oleic acid, hydroxytyrosol, and oleuropein—in the field of clinical nutrition and dietetics. The evidence is split into diet therapy, oleic acid-based enteral nutrition formulations and oral supplementation formulations, oleic acid-based parenteral nutrition, and nutraceutical supplementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 350 publications
(415 reference statements)
0
21
0
Order By: Relevance
“…In fact, the Mediterranean diet is recommended to patients, as it was shown to be effective for prevention of cardiovascular events [ 48 , 49 ]. Some components of the Mediterranean diet such as olive oil provide cardiovascular benefits, antithrombotic properties [ 50 , 51 ] and improves postprandial lipemia concentration, which is typically elevated in patients with T2DM [ 52 ]. In recent years, interest in functional components from herbal medicines has increased, supported by the confirmed medicinal potential of essential oils [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the Mediterranean diet is recommended to patients, as it was shown to be effective for prevention of cardiovascular events [ 48 , 49 ]. Some components of the Mediterranean diet such as olive oil provide cardiovascular benefits, antithrombotic properties [ 50 , 51 ] and improves postprandial lipemia concentration, which is typically elevated in patients with T2DM [ 52 ]. In recent years, interest in functional components from herbal medicines has increased, supported by the confirmed medicinal potential of essential oils [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…HTyr [ 71 , 72 ] and Tyr [ 73 ] are phenolic compounds specific to olive oil, while cinnamic acid [ 74 ], apigenin [ 75 ], and pinoresinol [ 76 ] are widespread and found in a great number of plants. All of these compounds are well known for their bioactive properties, such as antioxidant and antitumor activities, in addition to many others [ 77 , 78 ]. All analysed compounds were present in low concentrations, below 10 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…Along with the general suppression of the embryonic toxicity, the combined vitamin E and EVO treatment was also found to significantly improve the lambda-cyhalothrin exposure effects on embryonic growth retardation. These improvements in the growth parameters on vitamin E and EVO exposures along with the insecticide indicate that vitamin E in particular and the various precious antioxidants present in extra virgin olive oil have helped the developing embryo by providing a shield against reactive oxygen species that are usually produced in the developing tissues and organs on insecticide exposure [17] , [20] . The results of the present study suggest that use of EVO and vitamin E in the diets of farms animals and in aviaries, will increase the production rate of many expensive birds and provide protection against the exposure of most of the insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E and extra virgin olive oil being an ideal antioxidant protect tissues, proteins, lipids and DNA from oxidative stress because of their easy effective and safe dietary administration in large range of concentrations [12] , [20] , [26] . Various studies performed on rabbits and mice have shown that treatment with vitamin E alone caused significant increase in body weight and enhanced the immune functions [32] , [35] .…”
Section: Discussionmentioning
confidence: 99%